2021
DOI: 10.1158/1078-0432.ccr-20-2409
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Study of Coexpression Extrapolation (COXEN) with Neoadjuvant Chemotherapy for Bladder Cancer (SWOG S1314; NCT02177695)

Abstract: Purpose: Dose-dense Methotrexate-Vinblastine-Adriamycin-Cisplatin (ddMVAC) and Gemcitabine-Cisplatin (GC) are accepted neoadjuvant regimens for muscle-invasive bladder cancer (BC). The aim of this study was to validate the score from a Coexpression extrapolation (COXEN) algorithm-generated gene expression model (GEM) as a biomarker in patients undergoing radical cystectomy.Experimental Design: Eligibility included cT2-T4a N0 M0, urothelial BC, ≥ 5 mm of viable tumor, cisplatin eligible, with plan for cystectom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 15 publications
1
41
2
Order By: Relevance
“…However, in 2021, Pfister C. et al. performed the latest VESPER randomized phase III trial with a large sample size and prospectively demonstrated the superiority of ddMVAC ( 25 ), which was taken as strong evidence in our meta-analysis. The results of this large-scale clinical trial showed that although GC was more manageable with slighter asthenia and gastrointestinal side effects than ddMVAC, the latter had a higher local control rate and showed prominent advantage in pathological response.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, in 2021, Pfister C. et al. performed the latest VESPER randomized phase III trial with a large sample size and prospectively demonstrated the superiority of ddMVAC ( 25 ), which was taken as strong evidence in our meta-analysis. The results of this large-scale clinical trial showed that although GC was more manageable with slighter asthenia and gastrointestinal side effects than ddMVAC, the latter had a higher local control rate and showed prominent advantage in pathological response.…”
Section: Discussionmentioning
confidence: 81%
“…A total of 18 reports of 3116 patients receiving neoadjuvant chemotherapy were included, comprising 4 RCTs and 14 retrospective studies (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). All 18 articles provided comparative outcomes of PCR, in which seven studies had PPR outcomes and four studies conducted survival analyses.…”
Section: Researches Screening and Risk Bias Assessmentmentioning
confidence: 99%
“…** COXEN is an algorithm that predicts drug sensitivity of a previously analyzed panel of diverse cancer cell models. COXEN trial (NCT02177695) which was designed to assess the utility of a gene expression based biomarker to predict pathologic responses in patients receiving NAC showed similar results comparing ddMVAC and GC in a secondary analysis [27]. While VESPER will likely answer whether to use ddMVAC or GC, several different strategies are also being tested to improve outcomes from neoadjuvant therapy.…”
Section: Neoadjuvant Systemic Treatment Followed By Radical Cystectomy 3211 Standard Treatmentmentioning
confidence: 97%
“…According to one such study, basal tumors were observed to provide the most significant improvement in OS with NAC compared to surgery alone, whereas luminal tumors were associated with the best outcome regardless of perioperative treatment [ 40 ]. However, in a randomized, phase II SWOG S1314 study, the score generated based on gene expression profile failed to predict the response to NAC in patients undergoing radical cystectomy [ 41 ]. This and other studies suggest that additional factors beyond genetic profiles must be taken under consideration to predict the response to NAC.…”
Section: Evidence Synthesismentioning
confidence: 99%